An assessment of the Swaziland Vision 2022 strategic plan: opportunities and challenges - Shongwe, Thulie (University of the Free State)
Achieving sustainable development and sustainable improvement in the quality of life of the people is the ultimate goal of each and every government in the world. However, this requires setting up a plan of action to properly guide the governments throughout the whole process. Accordingly, the Government of Swaziland also aspired to achieve ‘first world status’ by the year 2022, aimed at improving the quality of life of the people through the use of the National Development Strategy / Vision 2022. The study therefore sought to assess the opportunities and challenges of the Swaziland Vision 2022 Strategic Plan with a focus on finding out progress made towards Vision 2022 attainment, challenges that have hindered successful implementation of the Strategy as well as opportunities available and strategies for improvement. The study used a descriptive research design and questionnaires were administered to eighty respondents who were purposefully selected and comprised of the Ministry of Economic Planning (Implementation Office), Parliament Portfolio Committee, Civil Society Organizations, Academics, Development Practitioners and Community Development Councillors. The data collected were categorized and classified into comparative ideas and opinions and presented in tables using simple percentage supplemented with actual statements from the respondents. The findings indicated that it will be hard for the country to achieve the first world status because people are still battling with the fulfilment of their basis needs, coupled with the misconceptions that the people have, insufficient resources, corruption, lack of civic education and the lack of citizen participation in decision making. The study also found out that opportunities exist in the regional and international partnerships that the country has, availability and existence of skilled/educated resources, fertile soil and availability of infrastructure to support implementation of the NDS/Vision 2022. The study recommend that civic education should be conducted to allow the people to fully understand and appreciate the NDS/Vision 2022 and that they should be involved in all development endeavours as well as associate freely to discuss their development. Another recommendation was that the distribution and allocation of the budget should be fair and concentrate on important aspects and areas.
Dissertation (MDS (Development Studies))--University of the Free State, 2017
Keywords: Sustainable development; Sustainable improvement; Quality of life; Swaziland; Strategic plan